Analysis of Determinants of the Subjective Welfare of the Elderly in Membwi District, Badung District - Dewa Made Basudewa; Made Kembar Sri Budhi (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
KThe subjective well-being of the elderly population is one of the focuses of attention in solving population problems, where the condition of the elderly population is a benchmark for the economic conditions of a region. The increasing problems of the elderly certainly require special attention and handling in the development process. The aim of this study; 1) analyze the simultaneous influence of education level, income, access to health, equal social interaction, and level of religiosity on the subjective well-being of the elderly in Mengwi District; 2) analyze the partial influence of education level, income, access to health, equal social interaction, and level of religiosity on the subjective well-being of the elderly in Mengwi District; 3) analyze the role of the level of religiosity in moderating the influence of equal social interactions on the subjective well-being of the elderly in Mengwi District. The population in this study was residents aged 60 years and over in Mengwi District, namely 19,294 people. Based on calculations using the Slovin formula, the total sample of elderly residents in Mengwi District was obtained as a total of 100 elderly residents from 20 villages/sub-districts in Mengwi District. Sampling was carried out using accidental sampling. Data collection methods were observation, structured interviews, in-depth interviews and data analysis using moderated regression analysis. The research results show; 1) level of education, income, access to health, equal social interaction, and level of religiosity simultaneously have a significant effect on the subjective well-being of the elderly in Mengwi District; 2) level of education, income, access to health, equal social interaction, and level of religiosity partially have a significant positive effect on the subjective well-being of the elderly in Mengwi District; 3) the level of religiosity moderates/weakens the influence of equal social interaction on the subjective well-being of the elderly in Mengwi District.